Finding a stable core in supervision from a distance: A Kurdish-Australian case study. Issue 2 (4th March 2022) - Huijser, Henk; Mandalawi, Sazan M.; Henderson, Robyn; Kek, Megan Yih Chyn A.
ABSTRACT: This paper's second author is a doctoral student, based in Erbil, in the Kurdistan Region of Iraq, whose study focuses on peer education in refugee camps in that region. The other three co-authors are her supervisors, whom, to date, she has not physically met. Yet, we have created and sustained a productive 'learning community' from a distance. In this paper, we provide a critical reflection on the way this supervision learning community has worked and continues to work. We analyse the elements that make this a productive partnership and team, whilst also addressing some of the challenges. We use each other's reflections to discuss the elements that contribute to effective supervision from a distance. This case study demonstrates that creating and sustaining a human-centred learning community of peers forms the crucial foundation of and for effective distance doctoral supervision that nurtures independence and agency.